Gel polymer electrolyte and electrochemical device including same

By using a matrix polymer formed by the use of specific hybrid aggregates, combined with lithium salt and non -water solvents, the problem of low conductivity and poor safety in the secondary battery in lithium secondary batteries in lithium secondary batteries is solved. And high -temperature stability lithium secondary battery.

CN119384748APending Publication Date: 2025-01-28LG ENERGY SOLUTION LTD

Patent Information

Application Number
CN202380047266.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2023-04-14
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing gel polymer electrolytes have problems with low lithium ion conductivity, reduced mechanical strength and short circuit risk in lithium secondary batteries, which affect the safety and performance of the battery.

Method used

The matrix polymer formed by a low polymer through a specific chemical agglomeration, combined with lithium salt and non -water solvents to form a new gel polymer electrolyte. This electrolyte enhances the freedom and conductivity of lithium ions through the three -dimensional network structure and fluoride, and increases high temperature durability.

Benefits of technology

Realize the battery resistance, increase lithium ion conductivity, enhance the stability of high voltage and high temperature, and improve the safety and performance of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384748A_ABST
    Figure CN119384748A_ABST
Patent Text Reader

Abstract

A gel polymer electrolyte is provided that includes a matrix polymer that includes an oligomer containing a fluorine-substituted polyether unit and at least one acrylate unit at an end thereof. According to the gel polymer electrolyte, the degree of freedom of lithium ions is increased by fixing and stabilizing anions, so that the effect of reducing battery resistance is achieved, and high lithium ion conductivity is achieved. In addition, the matrix polymer structure in the gel polymer electrolyte provides enhanced high-temperature durability, thereby allowing the manufacture of a lithium secondary battery having improved high-voltage high-temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Korean Patent Application No. 10-2022-0046564 filed in Korea on April 14, 2022. The present disclosure relates to a gel polymer electrolyte and a lithium secondary battery including the same. Background Art

[0002] As technology develops and the demand for mobile devices is increasing, secondary batteries as energy sources are increasingly in demand. Among such secondary batteries, lithium secondary batteries having high energy density and voltage have been commercialized and widely used.

[0003] A lithium secondary battery is obtained by the following process: applying a positive electrode active material and a negative electrode active material individually to a current collector, or forming each active material itself into a film shape having a sufficient length; then winding or stacking the resulting structure together with a separator as an insulator to provide an electrode assembly; introducing the electrode assembly into a can or a similar container; and injecting an electrolyte into the can or a similar container.

[0004] Lithium metal oxides have been used as positive electrode active materials, and lithium metal, lithium alloys, crystalline carbon or amorphous carbon or carbon composites have been used as negative electrode active materials. In addition, as electrolytes, liquid electrolytes, particularly ion-conductive liquid electrolytes containing salts dissolved in non-aqueous organic solvents, have been widely used.

[0005] However, as energy storage technology has received increasing attention, it is necessary to develop a secondary battery that can reduce size, reduce weight, allow high-capacity charging / discharging, and have high-temperature and high-voltage safety. Therefore, recently, the development of batteries using gel polymer electrolytes including gel polymers rather than liquid electrolytes has received increasing attention.

[0006] Generally speaking, it is well known that in the order of [liquid electrolyte < gel polymer electrolyte < solid polymer electrolyte], the safety of the battery is improved while the performance of the battery is reduced.

[0007] In other words, the gel polymer electrolyte has a disadvantage in that it shows low lithium ion conductivity compared to a liquid electrolyte including only a liquid electrolyte. In order to solve this problem, a method for reducing the thickness of the gel polymer electrolyte has been proposed. However, in this case, there are problems in terms of battery performance and safety, for example, when manufacturing a battery, mechanical strength is reduced, and a short circuit occurs between the positive electrode and the negative electrode having the gel polymer electrolyte.

[0008] Therefore, there is a need to develop a gel polymer electrolyte that can improve the safety and performance of batteries. Summary of the invention

[0009] Technical issues

[0010] The present disclosure is designed to solve the related first technical problem, and thus the present disclosure is directed to providing a gel polymer electrolyte that can provide enhanced high voltage stability and achieve the effect of reducing battery resistance.

[0011] In order to solve the second technical problem, the present disclosure also provides a composition for the gel polymer electrolyte.

[0012] In addition, in order to solve the third technical problem, the present disclosure is directed to providing a lithium secondary battery including the gel polymer electrolyte.

[0013] It will be easily understood that the objects and advantages of the present disclosure can be achieved by the means shown in the appended claims and combinations thereof.

[0014] Technical Solution

[0015] According to a first embodiment of the present disclosure, there is provided a gel polymer electrolyte including a matrix polymer and an electrolyte impregnated with the matrix polymer, wherein the matrix polymer is formed into a three-dimensional network structure by polymerization of an oligomer represented by the following Chemical Formula 1, the electrolyte includes a lithium salt and a non-aqueous solvent, and the non-aqueous solvent includes at least one selected from the group consisting of a cyclic carbonate-based compound, a linear carbonate-based compound, an alkyl ether-based compound, an alkyl acetate-based compound, an alkyl propionate-based compound, and a nitrile-based compound.

[0016] [Chemical formula 1]

[0017]

[0018] In the above chemical formula 1,

[0019] r is an integer of 1 or greater,

[0020] R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group,

[0021] R 2 and R 5 each independently represents a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom,

[0022] R 3 represents a Cn alkyl group in which all hydrogen atoms are replaced by fluorine atoms, R 4 represents a Cn-1 alkyl group in which all hydrogen atoms are replaced by fluorine atoms, and n is 2 or 3,

[0023] Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1,

[0024] R 6 and R 7 Each independently represents a C1 to C5 straight chain alkyl or branched chain alkyl,

[0025] R 8 is none or represents a methyl group, and m is an integer selected from 1, 2, 3, 4 and 5.

[0026] According to a second embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in the first embodiment, wherein the oligomer includes a unit A represented by the following Chemical Formula 2, a unit B represented by the following Chemical Formula 3, and a unit C represented by the following Chemical Formula 4.

[0027] [Chemical formula 2]

[0028]

[0029] [Chemical formula 3]

[0030]

[0031] [Chemical formula 4]

[0032]

[0033] In the above Chemical Formula 2, Chemical Formula 3 and Chemical Formula 4,

[0034] r is an integer of 1 or greater,

[0035] R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group,

[0036] R 2 and R 5 each independently represents a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom,

[0037] R 3 represents a Cn alkyl group in which all hydrogen atoms are replaced by fluorine atoms, R 4 represents a Cn-1 alkyl group in which all hydrogen atoms are replaced by fluorine atoms, and n is 2 or 3,

[0038] Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1,

[0039] R 6 and R 7Each independently represents a C1 to C5 straight chain alkyl or branched chain alkyl,

[0040] R 8 is none or represents a methyl group, and m is an integer selected from 1, 2, 3, 4 and 5.

[0041] According to a third embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in the second embodiment, wherein Chemical Formula 2 is divided into a unit represented by the following Chemical Formula 2-1 and a unit represented by the following Chemical Formula 2-2.

[0042] [Chemical formula 2-1]

[0043]

[0044] [Chemical formula 2-2]

[0045]

[0046] In the above chemical formula 2-2,

[0047] R 1 represents an aliphatic hydrocarbon group, an alicyclic hydrocarbon group or an aromatic hydrocarbon group.

[0048] According to a fourth embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in the third embodiment, wherein the aliphatic hydrocarbon group is a C1 to C20 alkylene group; a C1 to C20 alkylene group containing an isocyanate (NCO) group; a C1 to C20 alkoxyene group; a C2 to C20 alkene group; or a C2 to C20 alkynylene group;

[0049] The alicyclic hydrocarbon group is a substituted or unsubstituted C4 to C20 cycloalkylene group; a substituted or unsubstituted C4 to C20 cycloalkylene group containing an isocyanate (NCO) group; a C4 to C20 cycloalkenylene group; or a C2 to C20 heterocycloalkylene group; and

[0050] The aromatic hydrocarbon group is a substituted or unsubstituted C6 to C20 arylene group; or a C2 to C20 heteroarylene group.

[0051] According to a fifth embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in the fourth embodiment, wherein the structure represented by Chemical Formula 2-2 is derived from any one selected from compounds represented by the following Chemical Formulas a to n.

[0052] [Chemical formula a]

[0053]

[0054] [Chemical formula b]

[0055]

[0056] [Chemical formula c]

[0057]

[0058] [Chemical formula d]

[0059]

[0060] [Chemical formula e]

[0061]

[0062] [Chemical formula f]

[0063]

[0064] [Chemical formula g]

[0065]

[0066] [Chemical formula h]

[0067]

[0068] [Chemical formula i]

[0069]

[0070] [Chemical formula j]

[0071]

[0072] [Chemical formula k]

[0073]

[0074] [Chemical formula 1]

[0075]

[0076] [Chemical formula m]

[0077]

[0078] [Chemical formula n]

[0079]

[0080] According to a sixth embodiment of the present disclosure, there is provided the gel polymer electrolyte as defined in the fourth embodiment, wherein the structure represented by Chemical Formula 2-2 is any one selected from the following Chemical Formulae o to x.

[0081] [Chemical formula o]

[0082]

[0083] [Chemical formula p]

[0084]

[0085] [Chemical formula q]

[0086]

[0087] [Chemical formula]

[0088]

[0089] [Chemical formulas]

[0090]

[0091] [Chemical formula t]

[0092]

[0093] [Chemical formula]

[0094]

[0095] [Chemical formula v]

[0096]

[0097] [Chemical formula w]

[0098]

[0099] [Chemical formula x]

[0100]

[0101] According to a seventh embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in any one of the second to sixth embodiments, wherein Chemical Formula 4 provides (meth)acryloyl groups to both ends of the oligomer represented by Chemical Formula 1.

[0102] According to an eighth embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in any one of the first to seventh embodiments, wherein the oligomer includes a compound represented by the following Chemical Formula 5.

[0103] [Chemical formula 5]

[0104]

[0105] According to a ninth embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in any one of the first to eighth embodiments, wherein a weight average molecular weight (Mw) of the oligomer is about 1,000 to 500,000 g / mol.

[0106] According to a tenth embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in any one of the first to ninth embodiments, wherein the matrix polymer further includes inorganic particles in an amount of 5 to 700 parts by weight based on 100 parts by weight of the oligomer.

[0107] According to an eleventh embodiment of the present disclosure, there is provided a gel polymer electrolyte as defined in any one of the first to tenth embodiments, the gel polymer electrolyte having a gel content of about 1 wt % or more at a temperature of 25° C.

[0108] According to a twelfth embodiment of the present disclosure, there is provided a lithium ion secondary battery including a negative electrode, a positive electrode, and a gel polymer electrolyte, wherein the gel polymer electrolyte is the same as the gel polymer electrolyte defined in any one of the first to eleventh embodiments.

[0109] According to a thirteenth embodiment of the present disclosure, there is provided a composition for a gel polymer electrolyte, the composition including a lithium salt, a nonaqueous solvent, a polymerization initiator, and an oligomer represented by the following Chemical Formula 1, wherein the content of the oligomer is 0.5 wt % to 20 wt % based on the total weight of the composition for a gel polymer electrolyte,

[0110] [Chemical formula 1]

[0111]

[0112] In the above chemical formula 1,

[0113] r is an integer of 1 or greater,

[0114] R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group,

[0115] R 2 and R 5 each independently represents a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom,

[0116] R 3 represents a Cn alkyl group in which all hydrogen atoms are replaced by fluorine atoms, R 4 represents a Cn-1 alkyl group in which all hydrogen atoms are replaced by fluorine atoms, and n is 2 or 3,

[0117] Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1,

[0118] R 6 and R 7 Each independently represents a C1 to C5 straight chain alkyl or branched chain alkyl,

[0119] R 8 is none or represents a methyl group, and m is an integer selected from 1, 2, 3, 4 and 5.

[0120] Beneficial Effects

[0121] The gel polymer electrolyte according to the present disclosure includes a matrix polymer, the matrix polymer includes an oligomer, the oligomer contains a fluorine-substituted polyether unit and at least one acrylate unit at the end, thereby increasing the degree of freedom of Li ions by fixing and stabilizing anions to achieve the effect of reducing battery resistance, thereby achieving high lithium ion conductivity. In addition, the matrix polymer structure in the gel polymer electrolyte provides enhanced high temperature durability, thereby allowing the manufacture of a lithium secondary battery with improved high voltage high temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0122] The accompanying drawings illustrate preferred embodiments of the present disclosure and are used together with the following disclosure to provide a further understanding of the technical features of the present disclosure, and therefore, the present disclosure should not be interpreted as being limited to the drawings. At the same time, the shapes, sizes, scales, or proportions of some components in the drawings may be exaggerated for the purpose of a clearer description.

[0123] Figure 1 is a graph showing the results of heat dissipation safety tests of batteries according to Example 1 and Comparative Example 1 in comparison with each other.

[0124] Figure 2 is a graph showing the results of tests for evaluating the capacity retention ratio and resistance increase of the batteries according to Example 1 and Comparative Example 1 in comparison with each other.

[0125] Figure 3 The hot box test results of the battery according to Example 2 are shown.

[0126] Figure 4 Hot box test results of the battery according to Comparative Example 2 are shown.

[0127] Figure 5 Changes in capacity and thickness of the batteries according to Example 2 and Comparative Example 2 during repeated charge / discharge are shown.

[0128] Figure 6This is a photograph of the battery according to Example 2 undergoing a hot box test.

[0129] Figure 7 This is a photograph of the battery of Comparative Example 2 subjected to a hot box test. DETAILED DESCRIPTION

[0130] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before describing, it should be understood that the terms used in the specification and the accompanying claims should not be interpreted as being limited to the common meaning and dictionary meaning, but should be interpreted based on the meaning and concept of the technical aspects of the corresponding present disclosure on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented herein are only preferred examples for illustrative purposes and are not intended to limit the scope of the present disclosure, so it should be understood that other equivalents and improvements may be made thereto without departing from the scope of the present disclosure.

[0131] Throughout the specification, the expression "a portion includes or comprises an element" does not exclude the existence of any other elements, but means that the portion may further include other elements unless otherwise specified.

[0132] As used herein, the terms "approximately," "substantially," or the like, when implying acceptable manufacturing and material errors unique to the claimed meaning, are used to mean from or to the claimed numerical value, and are used to prevent unintentional infringers from improperly using the claimed disclosure, including exact or absolute numerical values ​​provided to aid understanding of the disclosure.

[0133] As used herein, the expression "A and / or B" means "A, B, or both."

[0134] Meanwhile, the term "repeating unit" used herein refers to a unit formed by polymerization of a monomer and derived therefrom. The repeating unit may be a unit directly formed by polymerization or a unit formed by treating a polymer so that its unit is partially converted into another structure.

[0135] Furthermore, unless otherwise specified, "*" used herein refers to a portion in which different atoms or terminals of a chemical formula are connected to each other.

[0136] In general, the disadvantages of gel polymer electrolytes are that they have lower high-voltage safety and mechanical properties compared to solid polymer electrolytes, and that they show poor cell resistance and lower ionic conductivity compared to liquid electrolytes.

[0137] Therefore, some research has been conducted recently to improve lithium ion conductivity while ensuring high voltage stability by using copolymers such as oligomers. However, when using oligomers, it is not easy to control physical properties and it is difficult to form polymers uniformly in the battery, which makes it difficult to apply gel polymer electrolytes to high-capacity and large-scale batteries.

[0138] Under these circumstances, according to the present disclosure, the above problems are solved by providing a gel polymer electrolyte including a matrix polymer formed of an oligomer compound prepared by polymerizing compounds having physical properties capable of complementing electrochemical characteristics and mechanical properties with each other.

[0139] In particular, in one aspect of the present disclosure, there is provided a gel polymer electrolyte comprising a matrix polymer; and

[0140] impregnating the matrix polymer with an electrolyte,

[0141] wherein the matrix polymer is formed into a three-dimensional network structure by polymerization of an oligomer represented by the following Chemical Formula 1,

[0142] And the oligomer includes a unit A represented by the following Chemical Formula 2, a unit B represented by the following Chemical Formula 3, and a unit C represented by the following Chemical Formula 4.

[0143] [Chemical formula 1]

[0144]

[0145] In the above chemical formula 1,

[0146] r is an integer of 1 or greater,

[0147] R 1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group,

[0148] R 2 and R 5 Each independently represents a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom, R 3 represents a Cn alkyl group in which all hydrogen atoms are replaced by fluorine atoms, R 4 represents a Cn-1 alkyl group in which all hydrogen atoms are replaced by fluorine atoms, and n is 2 or 3,

[0149] Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1,

[0150] R 6 and R 7Each independently represents a C1 to C5 straight chain alkyl or branched chain alkyl, and more particularly, R 6 represents a C2 to C4 straight chain alkyl or branched chain alkyl

[0151] R 8 is none or represents a methyl group, and m is an integer selected from 1, 2, 3, 4 and 5.

[0152] According to the present disclosure, the above 1 To R 7 The description of , r, p and q also applies to the following Chemical Formula 2, Chemical Formula 3, Chemical Formula 4 and Chemical Formula 5.

[0153] Hereinafter, the above Chemical Formula 1 will be explained in detail part by part with reference to the unit A (Chemical Formula 2), the unit B (Chemical Formula 3), and the unit C (Chemical Formula 4) forming Chemical Formula 1.

[0154] [Chemical formula 2]

[0155]

[0156] In the above Chemical Formula 2, p, q and r each represent the number of repeating units.

[0157] Herein, unit A may be divided into unit A-1 represented by the following chemical formula 2-1 and unit A-2 represented by the following chemical formula 2-2, and will be explained below with reference to chemical formula 2-1 and chemical formula 2-2. In chemical formula 2, r is an integer of 1 or more and may have a value of 1 to 20. The weight average molecular weight (Mw) of unit A represented by chemical formula 2 may be 100 to 100,000.

[0158] [Chemical formula 2-1]

[0159]

[0160] In the above chemical formula 2-1, R 2 and R 5 Each independently represents a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom. 3 represents a Cn alkyl group in which all hydrogen atoms are replaced by fluorine atoms, R 4 represents a Cn-1 alkyl group in which all hydrogen atoms are replaced by fluorine atoms, and n is 2 or 3. In Chemical Formula 2-1, either p or q represents 0, or both p and q may represent an integer of 1 or more. When both p and q represent an integer of 1 or more, the value of p / q may be 1 / 9 to 9 / 1.

[0161] [Chemical formula 2-2]

[0162]

[0163] In the above chemical formula 2-2, R 1 It may represent an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group.

[0164] According to an embodiment of the present disclosure, the aliphatic hydrocarbon group may be a C1 to C20 alkylene group; a C1 to C20 alkylene group containing an isocyanate (NCO) group; a C1 to C20 alkoxyene group; a C2 to C20 alkene group; or a C2 to C20 alkynylene group;

[0165] The alicyclic hydrocarbon group may be a substituted or unsubstituted C4 to C20 cycloalkylene group; a substituted or unsubstituted C4 to C20 cycloalkylene group containing an isocyanate (NCO) group; a C4 to C20 cycloalkenylene group; or a C2 to C20 heterocycloalkylene group; and

[0166] The aromatic hydrocarbon group may be a substituted or unsubstituted C6 to C20 arylene group; or a C2 to C20 heteroarylene group.

[0167] According to an embodiment of the present disclosure, the structure represented by Chemical Formula 2-2 may be derived from any one selected from the compounds represented by the following Chemical Formulas a to n.

[0168] [Chemical formula a]

[0169]

[0170] [Chemical formula b]

[0171]

[0172] [Chemical formula c]

[0173]

[0174] [Chemical formula d]

[0175]

[0176] [Chemical formula e]

[0177]

[0178] [Chemical formula f]

[0179]

[0180] [Chemical formula g]

[0181]

[0182] [Chemical formula h]

[0183]

[0184] [Chemical formula i]

[0185]

[0186] [Chemical formula j]

[0187]

[0188] [Chemical formula k]

[0189]

[0190] [Chemical formula 1]

[0191]

[0192] [Chemical formula m]

[0193]

[0194] [Chemical formula n]

[0195]

[0196] In particular, the unit A includes a fluorine-substituted ether in its structure, and thus can achieve the effects of improving high voltage safety, reducing resistance of the battery, and improving ion conductivity through anion stabilization and oxidation safety enhancement effects.

[0197] Meanwhile, according to an embodiment of the present disclosure, the structure represented by Chemical Formula 2-2 may be any one selected from the following Chemical Formulas o to x.

[0198] [Chemical formula o]

[0199]

[0200] [Chemical formula p]

[0201]

[0202] [Chemical formula q]

[0203]

[0204] [Chemical formula]

[0205]

[0206] [Chemical formulas]

[0207]

[0208] [Chemical formula t]

[0209]

[0210] [Chemical formula]

[0211]

[0212] [Chemical formula v]

[0213]

[0214] [Chemical formula w]

[0215]

[0216] [Chemical formula x]

[0217]

[0218] According to an embodiment of the present disclosure, unit B may be represented by the following Chemical Formula 3.

[0219] [Chemical formula 3]

[0220]

[0221] In the above Chemical Formula 3, the mark "*" present on both sides indicates a position linked to each of the above-mentioned unit A-1 and unit C described below. 1 For a detailed description, please refer to R in Chemical Formula 2-2 1 of the above description.

[0222] Meanwhile, according to an embodiment of the present disclosure, as described above, the structure represented by Chemical Formula 3 may be a structure represented by any one of Chemical Formulae o to x.

[0223] According to an embodiment of the present disclosure, unit C may be represented by Chemical Formula 4 below.

[0224] [Chemical formula 4]

[0225]

[0226] Herein, the unit C is bonded to both ends of the oligomer and provides functional groups capable of reacting with a crosslinking agent at both ends of the oligomer. 6 and R 7 Each may independently represent a C1 to C5 straight chain alkyl or branched chain alkyl. According to a particular embodiment, R 6 It can represent a C2 to C4 straight chain alkyl group or a branched chain alkyl group. 8is none or may represent a methyl group. In addition, m is an integer selected from 1, 2, 3, 4 and 5. In other words, the unit C can provide (meth)acryloyl groups to both ends of the oligomer.

[0227] In the gel polymer electrolyte according to the present disclosure, the oligomer may include a compound represented by the following Chemical Formula 5 as a typical example.

[0228] [Chemical formula 5]

[0229]

[0230] Hereinafter, the present disclosure will be explained in detail with reference to specific examples, but the following examples are only for illustrative purposes, and the scope of the present disclosure is not limited thereto.

[0231] The weight average molecular weight (Mw) of the oligomer used to form the gel polymer electrolyte according to the present disclosure may be about 1,000 g / mol to 500,000 g / mol, particularly 1,000 g / mol to 100,000 g / mol. When the weight average molecular weight of the oligomer falls within the above defined range, the mechanical strength of the battery including the oligomer can be effectively improved.

[0232] When the weight average molecular weight of the copolymer falls within the above-defined range, mechanical properties, processability (moldability), electrochemical stability, or similar properties can be ensured. In this article, in the unit A represented by the above chemical formula 1, p, q and r can be appropriately changed according to the weight average molecular weight of the copolymer within the above-defined range.

[0233] Herein, the weight average molecular weight can be determined by using gel permeation chromatography (GPC). For example, a sample having a predetermined concentration is prepared, and then the GPC analysis system, i.e., alliance 4 instrument, is stabilized. Once the instrument is stabilized, a reference sample and the sample are injected into the instrument to obtain a chromatogram, and the chromatogram is obtained according to the analysis method (system: Alliance 4, column: Ultrahydrogel linear×2, eluent: 0.1M NaNO 3 (pH 7.0 phosphate buffer), flow rate: 0.1 mL / min, temperature: 40°C, injection volume: 100 μL) to calculate the molecular weight.

[0234] Meanwhile, when the gel polymer electrolyte according to the present disclosure is implemented as a coating type gel polymer electrolyte, the matrix polymer may further include inorganic particles in an amount of 5 to 700 parts by weight, specifically 100 to 400 parts by weight, based on 100 parts by weight of the oligomer.

[0235] More preferably, the content of the inorganic particles is 700 parts by weight or less in order to effectively improve the problem of increased interfacial resistance with the electrode. When the content of the inorganic particles is greater than 700 parts by weight, pores are formed in the electrolyte, resulting in a decrease in ionic conductivity. When the content of the inorganic particles is less than 5 parts by weight, it is impossible to sufficiently improve the electrochemical stability while ensuring mechanical properties.

[0236] The matrix polymer allows the inorganic particles to be dispersed therein, so that the high-viscosity solvent can well penetrate through the pores formed between the inorganic particles. In other words, the effect of further improving the wettability with the high-viscosity solvent can be obtained through the affinity between the polar material and capillary action.

[0237] The inorganic particles that can be used herein include those having a high dielectric constant and not causing oxidation and / or reduction within the operating voltage range of applicable electrochemical devices (e.g., 0 - 5V based on Li / Li + . In particular, typical examples of the inorganic particles include any one selected from the group consisting of: BaTiO 3 , BaTiO 3 , Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT, where 0 < x < 1, 0 < y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O 3 - PbTiO 3 (PMN - PT), hafnium dioxide (HfO 2 ), SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2 O 3 , TiO 2 , SiC, lithium phosphate (Li 3 PO 4 ), lithium titanium phosphate (Li x1 Ti y1 (PO 4 ) 3 , 0 < x1 < 2, 0 < y1 < 3), lithium aluminum titanium phosphate (Li x2 Al y2 Tiz2 (PO 4 ) 3 , 0 < x2 < 2, 0 < y2 < 1, 0 < z2 < 3), such as 14Li 2 O - 9Al 2 O 3 - 38TiO 2 - 39P 2 O 5 of (LiAlTiP) x3 O y3 - based glass (0 < x3 < 4, 0 < y3 < 13), lithium lanthanum titanate (Li x4 La y4 TiO 3 , 0 < x4 < y4 < 3), such as Li 3.25 Ge 0.25 P 0.75 S of lithium germanium thiophosphate (Li x5 Ge y5 P z S w , 0 < x5 < 4, 0 < y5 < 1, 0 < z < 1, 0 < w < 5), such as Li 3 N of lithium nitride (Li x6 N y6 , 0 < x6 < 4, 0 < y6 < 2), such as Li 3 PO 4 - Li 2 S - SiS 2 of SiS 2 - based glass (Li x7 Si y7 S z2 , 0 < x7 < 3, 0 < y7 < 2, 0 < z2 < 4), such as LiI - Li 2 S - P 2 S 5 of P 2 S 5 - based glass (Li x8 P y8 S z3 , 0 < x8 < 3, 0 < z3 < 7), and lithium lanthanum zirconium oxide (Li 7 La 3 Zr 2 O 12 , LLZO), or a composition of two or more of them.

[0238] The average particle size of the inorganic particles is preferably about 0.001 μm to 10 μm so that they can be present in the gel polymer electrolyte with uniform thickness and suitable porosity. When the average particle size is less than 0.001 μm, the inorganic particles will show low dispersibility. When the average particle size is greater than 10 μm, the thickness of the porous coating will increase, and the inorganic particles will agglomerate, so the inorganic particles will be exposed to the outside of the gel polymer electrolyte and the mechanical strength will decrease. The gel polymer electrolyte according to the present disclosure can achieve a 2.5×10 -4 S / Cm or higher Li + Ionic conductivity. Herein, the ionic conductivity is determined by inserting the gel polymer electrolyte between a pair of platinum electrode disks having a diameter of 1 cm and then measuring the ionic conductivity of the gel polymer electrolyte by impedance analysis. The instrument used herein may be a VMP3 model purchased from Bio Logic Co., and the ionic conductivity may be measured at room temperature under the conditions of 10,000 Hz to 0.1 Hz and an amplitude of 10 mV.

[0239] In addition, the Li + The ion mobility coefficient can be 0.3 or higher. In this paper, Li + The ion migration coefficient can be defined as Li + Ion diffusion constant / (Li + Ion diffusion constant + anion diffusion constant), where Li + Ion diffusion constants and anion diffusion constants can be determined by the following methods and systems. For example, using a Varian 500 MHz NMR / dual probe, Li + The ion diffusion constant is given by 7 Li diffusion NMR is used to determine the anion diffusion constant. 19 F diffusion NMR is determined. The solvent used in this article is acetone-d6, and the sample is prevented from mixing with the deuterated solvent by using an inner tube (acetone-d6) to determine the diffusion value in the sample itself. In addition, in this experiment, stimulated echo with gradient pulses is used as a pulse sequence. The gradient amplitude is controlled in such a way that the peak intensity under the highest gradient power can be about 2% to 5% of the peak intensity under the lowest gradient power, and the corresponding range is divided into 16 steps in the same way as solution NMR, so that 16 different amplitudes can be applied to each sample.

[0240] In addition, the gel polymer electrolyte may have a gel content of about 1 wt % or more, for example about 20 wt % or more, at a temperature of 25° C. The gel content may refer to the weight of remaining components of the gel polymer electrolyte excluding the electrolyte.

[0241] Furthermore, the gel polymer electrolyte preferably shows an unreacted oligomer content of 20 wt % or less based on the total input of reactive oligomers at a temperature of 25°C.

[0242] Herein, the content of the unreacted oligomer may be determined by preparing a gel polymer electrolyte, extracting the gel polymer electrolyte with a solvent (acetone), and analyzing the extracted solvent by NMR.

[0243] Meanwhile, in the gel polymer electrolyte according to the present disclosure, the electrolyte impregnated with the matrix polymer includes a non-aqueous solvent containing a conventionally used lithium salt, wherein the lithium salt may be any one selected from the group consisting of: LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 CF 3 SO 3 Li、LiC(CF 3 SO 2 ) 3 ,LiC 4 BO 8 , LiTFSI, LiFSI and LiClO 4 , or a mixture of two or more thereof, but not limited thereto.

[0244] The lithium salt may be present in the electrolyte at a concentration of 1M to 2M, or in an amount of 10% to 50% by weight based on the total content of the oligomer. In addition, the electrolyte solvent used according to the present disclosure may be a non-aqueous solvent conventionally used for the electrolyte of a lithium secondary battery, and its typical examples include at least one compound selected from the following: cyclic carbonate-based compounds, linear carbonate-based compounds, alkyl ether-based compounds, alkyl acetate-based compounds, alkyl propionate-based compounds, and nitrile-based compounds. In this article, the cyclic carbonate-based compound may include at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and fluoroethylene carbonate (FEC).

[0245] The alkyl ether-based compound may include at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, and ethyl propyl ether.

[0246] The alkyl acetate-based compound may include at least one selected from the group consisting of methyl acetate, ethyl acetate, and propyl acetate.

[0247] The alkyl propionate-based compound may include at least one selected from the group consisting of methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.

[0248] The nitrile-based compound may include at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, hexanenitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl acetonitrile, 2-fluorobenzyl acetonitrile and 4-fluorobenzyl acetonitrile.

[0249] In particular, among carbonate-based electrolyte solvents, propylene carbonate and ethylene carbonate as cyclic carbonates are high-viscosity organic solvents with high dielectric constants, and can dissociate lithium salts in electrolytes well, so they can be preferably used. When such cyclic carbonates are used in a suitable mixing ratio in a mixture with a linear carbonate of low viscosity and low dielectric constant such as ethyl methyl carbonate, diethyl carbonate or dimethyl carbonate, an electrolyte with high electrical conductivity can be preferably prepared.

[0250] In addition, the electrolyte solvent may further include additives conventionally used in electrolytes to improve quality. For example, the electrolyte solvent may further include conventional additives such as vinylene carbonate (VC), 1,3-propane sultone (PS), succinonitrile (SN), vinyl sulfate (ESa), 1,3-propylene sulfone (PRS), fluoroethylene carbonate (FEC), adiponitrile (AND), LiPO 2 F 2 , lithium difluorobis(oxalato)phosphate (LiODFB), lithium bis(oxalato)borate (LiBOB), (trimethylsilyl)propyl phosphate (TMSPa), (trimethylsilyl)propylene phosphite (TMSPi), TEEPa, TFEPi, or the like, without particular limitation.

[0251] Although conventional electrolytes can cause metal ions eluted from the positive electrode to be deposited at the negative electrode, the gel polymer electrolyte according to the present disclosure includes a matrix polymer formed by an oligomer, so that the effects of improving mechanical properties, enhancing high voltage safety, reducing battery resistance and improving ionic conductivity can be ensured. Therefore, a lithium secondary battery with improved life and capacity characteristics can be obtained. In addition, a protective layer including a polymer can be formed on the surface of the positive and negative electrodes to suppress side reactions, enhance adhesion to the electrode and suppress gas generation in the battery at high temperatures by utilizing the anion stabilization of the polymer structure. In addition, the separator can be enhanced with a gel polymer electrolyte to provide improved penetration stability, and the effect of improving stability such as overcharge stability can be achieved by improving flame retardancy and reducing volatility.

[0252] In another aspect of the present disclosure, provided is a composition for a gel polymer electrolyte including a lithium salt, an electrolyte solvent, a polymerization initiator, and an oligomer including the above-mentioned units A to C.

[0253] The content of the oligomer may be 0.5 wt % to 20 wt %, preferably 0.5 wt % to 10 wt % based on the total weight of the composition for gel polymer electrolyte. When the content of the oligomer is less than 0.5 wt %, it is difficult to gel and achieve the characteristics of the gel polymer electrolyte. When the content of the oligomer is greater than 20 wt %, the resistance increases due to the excess of the oligomer, resulting in a decrease in battery performance.

[0254] Furthermore, the gel polymer electrolyte according to the present disclosure may be obtained from the composition for a gel polymer electrolyte by using a polymerization process known to those skilled in the art.

[0255] As the polymerization initiator used for the reaction, any conventional polymerization initiator known to those skilled in the art may be included.

[0256] Examples of polymerization initiators include, but are not limited to, organic peroxides or hydroperoxides such as benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, t-butyl peroxy-2-ethyl-hexanoate, cumyl hydroperoxide, and hydrogen peroxide; azo compounds such as 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN, 2,2'-azobis(iso-butyronitrile)), 2,2'-azobis(dimethylvaleronitrile) (AMVN, 2,2'-azobis(dimethyl valeronitrile)), or the like.

[0257] The polymerization initiator may be decomposed by heating, for example, at 30°C to 100°C, or may be decomposed at room temperature (5°C to 30°C) to form free radicals, and the polymerizable oligomer may react with the acrylate-based compound by free radical polymerization to form a gel polymer electrolyte.

[0258] In addition, the polymerization initiator may be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the oligomer. When the content of the polymerization initiator is greater than 5 parts by weight, there is a disadvantage in that gelation occurs too quickly during injection of the composition for a gel polymer electrolyte into a battery, or unreacted initiator remains and subsequently adversely affects battery performance. On the other hand, when the content of the polymerization initiator is less than 0.1 parts by weight, gelation cannot be sufficiently performed.

[0259] Meanwhile, as described above, the lithium salt may include any one selected from the group consisting of: LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 CF 3 SO 3Li、LiC(CF 3 SO 2 ) 3 ,LiC 4 BO 8 , LiTFSI, LiFSI and LiClO 4 , or a mixture of two or more thereof, but not limited thereto.

[0260] In addition, as described above, the electrolyte solvent may include a non-aqueous solvent conventionally used for the electrolyte of a lithium secondary battery. For example, the electrolyte solvent may include at least one compound selected from the group consisting of a cyclic carbonate-based compound, a linear carbonate-based compound, an alkyl ether-based compound, an alkyl acetate-based compound, an alkyl propionate-based compound, and a nitrile-based compound.

[0261] Among these compounds, typically, the electrolyte solvent may include a carbonate compound which is a cyclic carbonate, a linear carbonate, or a mixture thereof.

[0262] Furthermore, in order to further impart additional effects, such as the effects of improving gelation reaction efficiency and reducing resistance, the composition for gel polymer electrolyte according to an embodiment of the present disclosure may further include other additives capable of achieving these physical properties and known to those skilled in the art, in addition to the components described above, as appropriate.

[0263] As mentioned above, the additives may include conventional additives such as VC, VEC, PS, SN, AdN, ESa, PRS, FEC, LiPO 2 F 2 , LiODFB, LiBOB, TMSPa, TMSPi, TFEPa, TFEPi, or the like.

[0264] In yet another aspect of the present disclosure, there is provided a lithium secondary battery, comprising:

[0265] positive and negative electrodes; and

[0266] A polymer electrolyte is disposed between the positive electrode and the negative electrode.

[0267] The polymer electrolyte includes a gel polymer electrolyte according to the present disclosure.

[0268] The gel polymer electrolyte is formed by polymerizing the composition for gel polymer electrolyte according to conventional methods known to those skilled in the art. For example, the gel polymer electrolyte can be formed by in-situ polymerizing the composition for gel polymer electrolyte in a secondary battery.

[0269] According to a more preferred embodiment, the gel polymer electrolyte may be prepared by a method comprising the following steps: (a) inserting an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode into a battery case; and (b) injecting a composition for a gel polymer electrolyte according to the present disclosure into the battery case and polymerizing to form a gel polymer electrolyte.

[0270] This in-situ polymerization in lithium secondary batteries can be carried out by electron beam (E-beam), gamma ray and room temperature / high temperature aging process. According to an embodiment of the present disclosure, the in-situ polymerization can be carried out by thermal polymerization. In this article, the polymerization time can be about 2 minutes to 12 hours, and the thermal polymerization temperature can be set to 30°C to 100°C.

[0271] More specifically, in-situ polymerization in a lithium secondary battery can be performed by adding a predetermined amount of a polymerization initiator and an oligomer to an electrolyte containing a lithium salt, followed by mixing, and injecting the resulting electrolyte into a battery cell. Then, the injection port of the battery cell is sealed and heated at 40° C. to 80° C. for 1 to 20 hours to perform polymerization. In this way, the electrolyte containing a lithium salt is gelled, and then a gel polymer electrolyte is prepared.

[0272] The lithium secondary battery according to an embodiment of the present disclosure has a charging voltage of 3.0 V to 5.0 V, and exhibits excellent capacity characteristics in both a general voltage region and a high voltage region.

[0273] Meanwhile, according to the embodiments of the present disclosure, the electrode for forming the lithium secondary battery can be obtained by conventional methods known to those skilled in the art. For example, the electrode active material is mixed and stirred with a solvent and optionally with a binder, a conductive material and a dispersant to prepare a slurry, and then the slurry is applied (coated) to a collector made of a metal, followed by compression and drying to obtain an electrode.

[0274] The positive electrode can be obtained by forming a positive electrode mixture layer on a positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry containing a positive electrode active material, a binder, a conductive material, a solvent, etc. to a positive electrode current collector, followed by drying and pressing.

[0275] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of the positive electrode current collector include stainless steel, aluminum, nickel, titanium, calcined carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver, or the like.

[0276] The positive electrode active material may include a compound capable of reversible lithium insertion / deinsertion, and specific examples thereof may include a lithium composite metal oxide containing at least one metal such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium composite metal oxide may include a lithium manganese-based oxide (e.g., LiMnO 2 、LiMn 2 O 4 etc.), lithium cobalt-based oxides (such as LiCoO 2 etc.), lithium nickel-based oxides (such as LiNiO 2 etc.), lithium nickel manganese-based oxides (such as LiNi 1-Y9 Mn Y9 O 2 (where 0<Y9<1), LiMn 2-z4 Ni z4 O 4 (where 0<Z4<2), etc.), lithium nickel cobalt-based oxides (such as LiNi 1-Y10 Co Y10 O 2 (where 0<Y10<1), etc.), lithium manganese cobalt-based oxides (such as LiCo 1-Y11 Mn Y11 O 2 (where 0<Y11<1), LiMn 2-z5 Co z5 O 4 (where 0<Z5<2), etc.), lithium nickel manganese cobalt-based oxides (such as Li(Ni a Co b Mn c ) 2 (where 0<a<1, 0<b<1, 0<c<1, and a+b+c=1), Li(Ni a1 Co b1 Mn c1 ) 4 (where 0<a1<2, 0<b1<2, 0<c1<2, and a1+b1+c1=2), etc.), lithium nickel cobalt transition metal (M) oxides (e.g. Li(Ni a2 Co b2 Mn c2 M d ) 2 (wherein M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, a2, b2, c2, and d each represent the atomic fraction of each individual element, 0<a2<1, 0<b2<1, 0<c2<1, 0<d<1, and a2+b2+c2+d=1), etc.), or the like, and any one compound or two or more compounds thereof can be used.

[0277] Among these materials, lithium composite oxides may include LiCoO in consideration of improvement in capacity characteristics and stability of the battery. 2 、LiMnO 2 、LiNiO 2 , lithium nickel manganese cobalt oxide (e.g. Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 ) 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.5 Mn 0.3 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 、Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 etc.), nickel-manganese-cobalt-aluminum compounds (e.g. Li(Ni 0.86 Mn 0.045 CoAl 0.045 Al 0.05 ) 2 ), lithium nickel cobalt aluminum oxide (e.g. Li(Ni 0.8 Co 0.15 Al 0.05 ) 2 etc.), or the like.

[0278] The positive electrode active material may be present in an amount of 80 wt % to 99 wt % based on the total weight of the solid content of the positive electrode slurry.

[0279] The binder is a component that assists the bonding between the active material and the conductive material and the bonding with the current collector. In general, the binder is added in an amount of 1% to 30% by weight based on the total weight of the solid content of the positive electrode slurry. Specific examples of binders include: polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, various copolymers, or the like.

[0280] The conductive material is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solid content of the positive electrode slurry.

[0281] The conductive material is not particularly limited as long as it has conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of the conductive material include: graphite; carbonaceous materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; carbon fluoride; metal powders such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium dioxide; conductive materials such as polyphenylene derivatives; or the like. Specific examples of commercially available products of conductive materials may include acetylene black (available from Chevron Chemical Company), denka black (available from Denka Singapore Private Limited or Gulf Oil Company), ketjen black EC (available from Armak Company), Vulcan XC-72 (available from Cabot Company), Super P (available from MMM Company), or the like.

[0282] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be added in such an amount that the solvent including the positive electrode active material optionally with a binder, a conductive material, etc. may have a desired viscosity level. For example, the solvent may be added in such a manner that the solid content of the slurry including the positive electrode active material optionally with a binder, a conductive material, etc. may be 40 wt % to 60 wt %, preferably 40 wt % to 50 wt %.

[0283] In addition, the negative electrode can be obtained by forming a negative electrode mixture layer on a negative electrode current collector. The negative electrode mixture layer can be formed by applying a negative electrode slurry containing a negative electrode active material, a binder, a conductive material, a solvent, etc. to a negative electrode current collector, followed by drying and pressing.

[0284] The negative electrode current collector generally has a thickness of 3 μm to 500 μm. The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of negative electrode current collectors include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel, aluminum-cadmium alloy or the like that has been surface-treated with carbon, nickel, titanium, silver, etc. In addition, similar to the positive electrode current collector, a fine surface random body can be formed on the surface of the negative electrode current collector to increase the binding force of the negative electrode active material. For example, the negative electrode current collector can have various shapes such as a film, a sheet, a foil, a net, a porous body, a foam or a non-woven mesh.

[0285] In addition, the negative electrode active material may include any one selected from the group consisting of: lithiated titanium composite oxide (LTO); carbonaceous materials such as non-graphitized carbon or graphite-based carbon; metal composite oxides such as Li x10 Fe 2 O 3 (0 ≤ x10 ≤ 1), Li x11 WO 2 (0 ≤ x11 ≤ 1) and Sn x12 Me 1-x12 Me’ y12 O z12 (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Group 1, 2 or 3 of the periodic table, halogens; 0 < x12 ≤ 1; 1 ≤ y12 ≤ 3; 1 ≤ z12 ≤ 8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO 2 、PbO、PbO 2 、Pb 2 O 3 、Pb 3 O 4 、Sb 2 O 3 、Sb 2 O 4 、Sb 2 O 5 、GeO、GeO 2 、Bi 2 O 3 、Bi 2 O 4 和Bi 2 O 5 ; and conductive polymers such as polyacetylene; or a mixture of two or more of them.

[0286] The negative electrode active material may be used in an amount of 80% by weight to 99% by weight based on the total weight of the solid content of the negative electrode paste.

[0287] The binder is a component that aids in the binding between the conductive material, the active material, and the current collector. Generally, the binder is added in an amount of 1% by weight to 30% by weight based on the total weight of the solid content of the negative electrode paste. Specific examples of the binder include: polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers thereof, or the like.

[0288] The conductive material is a component for further improving the conductivity of the negative electrode active material, and can be added in an amount of 1% to 20% by weight based on the total weight of the solid content of the negative electrode slurry. The conductive material is not particularly limited as long as it has conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of conductive materials include: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers, such as carbon fibers or metal fibers; carbon fluoride; metal powders, such as aluminum powder or nickel powder; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium dioxide; conductive materials, such as polyphenylene derivatives; or the like.

[0289] The solvent may include water or an organic solvent such as N-methyl-2-pyrrolidone (NMP), alcohol, or the like, and may be added in such an amount that the solvent including the negative electrode active material optionally with a binder, a conductive material, etc. may have a desired viscosity level. For example, the solvent may be added in such a manner that the solid content of the slurry including the negative electrode active material optionally with a binder, a conductive material, etc. may be 50 wt % to 75 wt %, preferably 50 wt % to 65 wt %.

[0290] Then, a separator is introduced between the positive electrode and the negative electrode.

[0291] The separator is used to interrupt the internal short circuit between the two electrodes and allow wetting with electrolyte. The separator film can be formed by mixing a polymer resin, a filler, and a solvent to prepare a separator composition, and coating the separator composition directly on top of the electrode, followed by drying. In one variation, the separator composition can be cast and dried on a support, and the separator film peeled from the support can be laminated on top of the electrode.

[0292] The polymer resin is not particularly limited. For example, a sheet or nonwoven web made of an olefin-based polymer such as polypropylene having chemical resistance and hydrophobicity; a composite porous separator including an inorganic material added to a porous separator substrate; a sheet or nonwoven web made of glass fiber or polyethylene; or the like can be used.

[0293] Generally speaking, the porous separator may have a pore size of 0.01 μm to 50 μm, a porosity of 5% to 95%, and a thickness of 5 μm to 300 μm.

[0294] There is no particular limitation on the outer shape of the lithium secondary battery according to the embodiment of the present disclosure. For example, the lithium secondary battery may have a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape.

[0295] Example

[0296] Example 1 (positive electrode active material NCMA)

[0297] (1) Preparation of composition for gel polymer electrolyte

[0298] First, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7, and 0.5 M LiPF 6 And 0.5M LiFeSI are introduced into the resulting mixture to prepare a mixed solvent. Next, an oligomer based on Chemical Formula 5 (weight average molecular weight 6000, p:q=2:1, r=3) is introduced to a content of 5% by weight of a composition for a gel polymer electrolyte accounting for 100% by weight. In addition, 0.1% by weight of a polymerization initiator (AIBN), 1.5% by weight of vinylene carbonate (VC) and 1% by weight of propane sultone (PS) are added thereto to prepare a composition for a gel polymer electrolyte. Table 1 below shows the components of a composition for a gel polymer electrolyte according to Example 1 and the content of each component.

[0299] [Table 1]

[0300]

[0301] (2) Manufacturing of lithium secondary batteries

[0302] First, 94 wt% of LiNi as the positive electrode active material 0.86 Co 0.045 Mn 0.045 Al 0.05 O 2 , 3 wt % of carbon black as a conductive material and 3 wt % of polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum (Al) foil having a thickness of about 20 μm as a positive electrode collector and dried, followed by roll pressing to obtain a positive electrode.

[0303] In addition, 96 wt % of carbon powder as a negative electrode active material, 3 wt % of PVDF as a binder, and 1 wt % of carbon black as a conductive material were added to NMP as a solvent to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) foil having a thickness of 10 μm as a negative electrode collector and dried, followed by roll pressing to obtain a negative electrode.

[0304] An electrode assembly was obtained using a positive electrode, a negative electrode, and a separator including three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). Then, the composition for gel polymer electrolyte prepared as described above was injected into the electrode assembly, the electrode assembly was allowed to stand for 2 days, and then heated at 60° C. for 24 hours to obtain a lithium secondary battery including a gel polymer electrolyte. The nominal voltage of the resulting battery was 2.5V to 4.2V.

[0305] Example 2 (positive electrode active material LCO)

[0306] (1) Preparation of composition for gel polymer electrolyte

[0307] A composition for a gel polymer electrolyte was prepared in the same manner as in Example 1, except that the composition shown in Table 2 below was used.

[0308] [Table 2]

[0309]

[0310] (2) Manufacturing of lithium secondary batteries

[0311] First, 94 wt% of LiCoO as the positive electrode active material was added. 2 (LCO), 3 wt % of carbon black as a conductive material, and 3 wt % of polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum (Al) foil having a thickness of about 20 μm as a positive electrode collector and dried, followed by roll pressing to obtain a positive electrode.

[0312] In addition, 96 wt % of carbon powder as a negative electrode active material, 3 wt % of PVDF as a binder, and 1 wt % of carbon black as a conductive material were added to NMP as a solvent to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) foil having a thickness of 10 μm as a negative electrode collector and dried, followed by roll pressing to obtain a negative electrode.

[0313] An electrode assembly was obtained using a positive electrode, a negative electrode, and a separator including three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). Then, the composition for gel polymer electrolyte prepared as described above was injected into the electrode assembly, the electrode assembly was allowed to stand for 2 days, and then heated at 60° C. for 24 hours to obtain a lithium secondary battery including a gel polymer electrolyte. The nominal voltage of the resulting battery was 3.0V to 4.45V.

[0314] Example 3 (positive electrode active material LFP)

[0315] (1) Preparation of composition for gel polymer electrolyte

[0316] First, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:4:3, and 1 M LiPF 6 Introduce into the resulting mixture to prepare a mixed solvent. Next, an oligomer based on Chemical Formula 5 (weight average molecular weight 6000, p: q = 2: 1, r = 3) is introduced to a content of 3% by weight of a composition for a gel polymer electrolyte accounting for 100% by weight. In addition, 0.1% by weight of a polymerization initiator (AIBN) and 2.5% by weight of vinylene carbonate (VC) are added thereto to prepare a composition for a gel polymer electrolyte. Table 3 below shows the components of a composition for a gel polymer electrolyte according to Example 3 and the content of each component.

[0317] [Table 3]

[0318]

[0319] (2) Manufacturing of lithium secondary batteries

[0320] First, 94 wt% of LiFePO as the positive electrode active material 4 (LFP), 3 wt % of carbon black as a conductive material and 3 wt % of polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum (Al) foil having a thickness of about 20 μm as a positive electrode collector and dried, followed by roll pressing to obtain a positive electrode.

[0321] In addition, 96 wt % of carbon powder as a negative electrode active material, 3 wt % of PVDF as a binder, and 1 wt % of carbon black as a conductive material were added to NMP as a solvent to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) foil having a thickness of 10 μm as a negative electrode collector and dried, followed by roll pressing to obtain a negative electrode.

[0322] An electrode assembly was obtained using a positive electrode, a negative electrode and a separator including three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). Then, the composition for gel polymer electrolyte prepared as described above was injected into the electrode assembly, the electrode assembly was allowed to stand for 2 days, and then heated at 60° C. for 24 hours to obtain a lithium secondary battery including a gel polymer electrolyte. The nominal voltage of the resulting battery was 2.5V to 3.6V. The capacity of the battery was 720mAh.

[0323] Comparative Example 1 (Using Liquid Electrolyte NCMA)

[0324] (1) Preparation of liquid electrolyte

[0325] First, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7, and 1 M LiPF 6 Introduced into the resulting mixture to prepare a mixed solvent. Then, 1.6 g VC and 1.5 g PS as other additives were added to 97 g of the mixed solvent to prepare a liquid electrolyte. Table 4 below shows the components of the composition for electrolyte according to Comparative Example 1 and the content of each component.

[0326] [Table 4]

[0327] Liquid electrolyte 100 wt% <![CDATA[EC and EMC (LiPF 6 1M)]]> 97% by weight Oligomer of Chemical Formula 5 (weight average molecular weight 6000) 0% by weight Polymerization initiator (AIBN) 0% by weight Vinylene carbonate (VC) 1.5 wt% PS (propane sultone) 1 wt%

[0328] (2) Manufacturing of lithium secondary batteries

[0329] First, 94 wt% of LiNi as the positive electrode active material 0.86 Co 0.045 Mn 0.045 Al 0.05 O 2 , 3 wt % of carbon black as a conductive material and 3 wt % of polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum (Al) foil having a thickness of about 20 μm as a positive electrode collector and dried, followed by roll pressing to obtain a positive electrode.

[0330] In addition, 96 wt % of carbon powder as a negative electrode active material, 3 wt % of PVDF as a binder, and 1 wt % of carbon black as a conductive material were added to NMP as a solvent to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) foil having a thickness of 10 μm as a negative electrode collector and dried, followed by roll pressing to obtain a negative electrode.

[0331] An electrode assembly was obtained using a positive electrode, a negative electrode, and a separator including three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). Then, the liquid electrolyte prepared as described above was injected into the electrode assembly to obtain a lithium secondary battery.

[0332] Comparative Example 2 (Using Liquid Electrolyte LCO)

[0333] A lithium secondary battery was obtained in the same manner as in Comparative Example 1, except that LiCoO 2 (LCO) as the positive electrode active material.

[0334] Comparative Example 3 (Using Liquid Electrolyte LFP)

[0335] (1) Preparation of liquid electrolyte

[0336] The liquid electrolyte was prepared by using the composition shown in Table 5 below.

[0337] [Table 5]

[0338] Liquid electrolyte 100 wt% <![CDATA[EC, DMC and EMC (LiPF 6 1M)]]> 97.5% by weight Vinylene carbonate (VC) 2.5 wt%

[0339] (2) Manufacturing of lithium secondary batteries

[0340] First, 94 wt% of LiFePO as the positive electrode active material 4 (LFP), 3 wt % of carbon black as a conductive material and 3 wt % of polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum (Al) foil having a thickness of about 20 μm as a positive electrode collector and dried, followed by roll pressing to obtain a positive electrode.

[0341] In addition, 96 wt % of carbon powder as a negative electrode active material, 3 wt % of PVDF as a binder, and 1 wt % of carbon black as a conductive material were added to NMP as a solvent to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) foil having a thickness of 10 μm as a negative electrode collector and dried, followed by roll pressing to obtain a negative electrode.

[0342] An electrode assembly was obtained using a positive electrode, a negative electrode, and a separator including three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). Then, the liquid electrolyte prepared as described above was injected into the electrode assembly to obtain a lithium secondary battery. The nominal voltage of the resulting battery was 2.5V to 3.6V. The capacity of the battery was 720mAh.

[0343] Comparative Example 4 (Using Gel Polymer Electrolyte LFP)

[0344] (1) Preparation of composition for gel polymer electrolyte

[0345] First, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:4:3, and 1 M LiPF 6 Introduce into the resulting mixture to prepare a mixed solvent. Next, the oligomer represented by the following chemical formula z (weight average molecular weight 6000, m2:n2=2:1, o2=6) is introduced to a content of 3 wt % of the composition for gel polymer electrolyte accounting for 100 wt %. In addition, 0.1 wt % of a polymerization initiator (AIBN) and 2.5 wt % of vinylene carbonate (VC) are added thereto to prepare a composition for gel polymer electrolyte.

[0346] [Chemical formula z]

[0347]

[0348] In the chemical formula CE4, m2, n2 and o2 each represent the number of repeating units, m2 is an integer from 1 to 10, n2 is an integer from 1 to 10, and o2 is an integer from 1 to 500.

[0349] [Table 6]

[0350]

[0351] (2) Manufacturing of lithium secondary batteries

[0352] First, 94 wt% of LiFePO as the positive electrode active material 4 (LFP), 3 wt % of carbon black as a conductive material and 3 wt % of polyvinylidene fluoride (PVDF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum (Al) foil having a thickness of about 20 μm as a positive electrode collector and dried, followed by roll pressing to obtain a positive electrode.

[0353] In addition, 96 wt % of carbon powder as a negative electrode active material, 3 wt % of PVDF as a binder, and 1 wt % of carbon black as a conductive material were added to NMP as a solvent to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to a copper (Cu) foil having a thickness of 10 μm as a negative electrode collector and dried, followed by roll pressing to obtain a negative electrode.

[0354] An electrode assembly was obtained using a positive electrode, a negative electrode and a separator including three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). The composition for gel polymer electrolyte prepared as described above was then injected into the electrode assembly, the electrode assembly was allowed to stand for 2 days, and then heated at 60° C. for 24 hours to obtain a lithium secondary battery including a gel polymer electrolyte. The nominal voltage of the resulting battery was 2.5 V to 3.6 V. The capacity of the battery was 720 mAh.

[0355] [Test example]

[0356] Test Example 1: Test of heat dissipation stability (Example 1 and Comparative Example 1)

[0357] After manufacturing each battery, additional heat emission was observed, along with a temperature increase in the fully charged state of the battery.

[0358] The heat flux was examined by using multiple module calorimetry (MMC) at a heating rate of 0.2 °C / min to 300 °C. Figure 1 As shown in Table 7, the first peak appears at 137.4 J in Example 1 and 156.9 J in Comparative Example 1, and the second peak appears at 127.4 J in Example 1 and 166.4 J in Comparative Example 1.

[0359] [Table 7]

[0360] First Peak(J) Second Peak (J) Example 1 137.4 127.4 Comparative Example 1 156.9 166.4

[0361] In the case of the beaker battery according to Example 1, it can be seen that the current increases rapidly in a lower voltage region than in a voltage region where a conventional electrolyte decomposes. It is believed that this is because the overcharge preventing agent contained in the electrolyte is decomposed, resulting in an increase in current (A). In contrast, in the case of the beaker battery according to Comparative Example 1, it can be seen that the current increases in a higher voltage region than in Example 1.

[0362] Test Example 2: Test for evaluation of high temperature capacity retention and resistance increase (Example 1 and Comparative Example 1)

[0363] The batteries according to Example 1 and Comparative Example 1 were charged to SOC 100% and maintained at 60° C. for 4 weeks.

[0364] The capacity retention rate is determined as follows. When the test is started, the battery is charged to 4.2V and discharged to 2.5V at 1C in a 60°C constant temperature chamber, and the capacity at this time point is measured. Then, the battery is placed in the chamber, charged to 4.2V and discharged to 2.5V at 1C at predetermined intervals, and the capacity is measured at each stage. This process is carried out for 4 weeks. The initial capacity is taken as 100%, and then each capacity value measured subsequently is calculated in % based on the initial capacity.

[0365] Meanwhile, the resistance increase was determined as follows. By using the HPPC Hybrid Pulse Power characterization method, the respective batteries according to Example 1 and Comparative Example 1 were pulse-discharged (DC-IR detector) at each SOC region to record the resistance, and the voltage change occurring during the discharge was divided by the discharge current, as shown in the following Formula 1, to calculate the resistance.

[0366] [Formula 1]

[0367] R=V / I

[0368] Where R represents resistance, V represents the voltage change during discharge, and I represents the discharge current.

[0369] [Table 8]

[0370] Capacity retention rate (%, 4 weeks) Resistance increase (%, 4 weeks) Example 1 96.7% 7.9% Comparative Example 1 96.7% 7.9%

[0371] The results are shown in Table 8 and Figure 2 From Table 8 and Figure 2 As can be seen in FIG. 1 , the gel polymer electrolyte according to the present disclosure does not affect the capacity or resistance of the battery compared to using a liquid electrolyte.

[0372] Test Example 3: Evaluation of Low-temperature Life Characteristics (Example 2 and Comparative Example 2)

[0373] Each of the batteries according to Example 2 and Comparative Example 2 was charged / discharged at a temperature of 15° C. to determine the capacity.

[0374] -Charging conditions: 2C, constant current (CC) / constant voltage (CV) (4.45V, 0.05C current cutoff)

[0375] -Discharge conditions: 1C, CC conditions, 3V

[0376] Then, the battery was charged / discharged repeatedly 200 times within the same current and voltage range.

[0377] The capacity retention rate is calculated according to the following mathematical formula 1:

[0378] [Mathematical formula 1]

[0379] Capacity retention rate (%) = [discharge capacity at the 200th cycle / charge capacity at the 1st cycle] × 100

[0380] Test Example 4: Evaluation of Room Temperature Life Characteristics (Example 2 and Comparative Example 2)

[0381] Each of the batteries according to Example 2 and Comparative Example 2 was charged / discharged at a temperature of 25° C. to determine the capacity.

[0382] -Charging conditions: 2C, constant current (CC) / constant voltage (CV) (4.45V, 0.05C current cutoff)

[0383] -Discharge conditions: 1C, CC conditions, 3V

[0384] Then, the battery was charged / discharged repeatedly 300 times within the same current and voltage range.

[0385] The capacity retention rate is calculated according to the following mathematical formula 2:

[0386] [Mathematical formula 2]

[0387] Capacity retention rate (%) = [discharge capacity at the 300th cycle / charge capacity at the 1st cycle] × 100

[0388] [Table 9]

[0389]

[0390] Referring to Table 9, the battery according to Example 2 achieves an equivalent level of capacity retention compared to a battery using a conventional liquid electrolyte. In particular, the battery according to Example 2 shows a significantly higher capacity retention after repeated charge / discharge under low temperature conditions than the battery of Comparative Example 2.

[0391] Test Example 5: High Temperature Storage Characteristics (Example 2 and Comparative Example 2)

[0392] Each battery according to Example 2 and Comparative Example 2 was left standing in a chamber under conditions of a temperature of 60° C. and a relative humidity of 90% for 7 days, and was evaluated with respect to a capacity retention rate and a capacity recovery rate.

[0393] The capacity retention rate is determined as follows. When the test is started, the battery is charged / discharged once under the charge / discharge conditions described in Test Example 4, and the capacity is measured. Then, the battery is left to stand in a chamber at a temperature of 60°C and a relative humidity of 90% for 7 days, then taken out of the chamber, charged to 4.45V at 0.2C and discharged to 3V, and the capacity is measured. The capacity initially measured is taken as 100%, and the residual capacity is calculated in %.

[0394] After that, each battery was allowed to stand at room temperature for a predetermined time, and charged / discharged to 3V to 4.45V at 0.2C and 0.1C, and the capacity was measured. Then, the capacity ratio based on the initial measured capacity (taking the value as 100%) was calculated to determine the capacity recovery rate (%).

[0395] [Table 10]

[0396]

[0397]

[0398] Referring to Table 10, the battery according to Example 2 achieves an equivalent level of capacity retention compared to a battery using a conventional liquid electrolyte. In particular, the battery according to Example 2 shows a significantly higher capacity retention after repeated charge / discharge under high temperature conditions than the battery of Comparative Example 2.

[0399] Test Example 6: Overview of Hot Box (Example 2 and Comparative Example 2)

[0400] The respective batteries according to Example 2 and Comparative Example 2 were subjected to a hot box test.

[0401] Each battery according to Example 2 and Comparative Example 2 was charged to SOC 100%, introduced into a chamber capable of controlling temperature, heated to 140° C. at a rate of 5° C. / min, and maintained at the same temperature for at least 1 hour. Figure 3 and Figure 4 Hot box test results of the battery according to Example 2 and the battery according to Comparative Example 2 are shown respectively.

[0402] As can be seen from the results, the battery according to Example 2 showed a longer voltage retention time than the battery according to Comparative Example 2. However, the battery according to Comparative Example 2 caused a rapid increase in temperature after 30 minutes, resulting in an explosion and thus failing to operate. This indicates that the battery according to Example 2 has higher heat resistance than the battery according to Comparative Example 2.

[0403] Figure 6 This is a photograph of the battery according to Example 2 undergoing a hot box test. Figure 7 This is a photo of the hot box test of the battery in Comparative Example 2. Figure 7 The battery shown was damaged due to its explosion.

[0404] Test Example 7: Comparison of Life Characteristics and Thickness Increase (Example 2 and Comparative Example 2)

[0405] The respective batteries according to Example 2 and Comparative Example 2 were charged / discharged at a temperature of 25° C. to determine the capacity. Each battery was charged to 4.45 V in a constant current (CC) / constant voltage (CV) mode while changing the rate to 2C, 1.5C, and 1C with a cutoff current of 0.05C. Each battery was discharged to 3 V at 1C in the CC mode. The charge / discharge cycle was repeated 400 times under the same conditions.

[0406] Figure 5 The capacities of the respective batteries according to Example 2 and Comparative Example 2 are shown. It can be seen that the battery according to Example 2 and the battery according to Comparative Example 2 show similar capacity changes. In addition, the battery according to Example 2 and the battery according to Comparative Example 2 both show a capacity retention rate of 78% at the 400th cycle. In addition, at the 400th cycle, the battery according to Example 2 and the battery according to Comparative Example 2 show a thickness increase of less than 5.76 nm. Therefore, it can be seen that the battery according to Example 2 has an equivalent level of electrochemical characteristics compared to a battery using a conventional liquid electrolyte.

[0407] Test Example 8 (Example 3 and Comparative Examples 3 and 4)

[0408] Each battery according to Example 3 and Comparative Examples 3 and 4 was charged / discharged three times to 2.5 V to 3.6 V and maintained at SOC 100% for 6 weeks in a constant temperature chamber at 60° C. Then, the room temperature resistance was measured at SOC 50%, and the resistance increase was determined based on the resistance of the initial battery.

[0409] [Table 11]

[0410]

[0411] The battery according to the present disclosure effectively suppresses the reaction between the electrode and the additive / electrolyte, and thus shows further improvement in resistance increase.

Claims

1. A gel polymer electrolyte comprising a matrix polymer and an electrolyte impregnated with the matrix polymer, wherein the matrix polymer is formed into a three-dimensional network structure by polymerization of an oligomer represented by the following Chemical Formula 1, The electrolyte includes a lithium salt and a non-aqueous solvent, and The non-aqueous solvent includes at least one selected from the group consisting of cyclic carbonate-based compounds, linear carbonate-based compounds, alkyl ether-based compounds, alkyl acetate-based compounds, alkyl propionate-based compounds, and nitrile-based compounds: [Chemical formula 1] In the above chemical formula 1, r is an integer of 1 or greater, R1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom, R3 represents a Cn alkyl group in which all hydrogen atoms are substituted by fluorine atoms, R4 represents a Cn-1 alkyl group in which all hydrogen atoms are substituted by fluorine atoms, and n is 2 or 3, Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1, R6 and R7 each independently represent a C1 to C5 straight chain alkyl or branched chain alkyl, R8 is null or represents methyl, and m is an integer selected from 1, 2, 3, 4 and 5.

2. The gel polymer electrolyte according to claim 1, wherein the oligomer comprises a unit A represented by the following Chemical Formula 2, a unit B represented by the following Chemical Formula 3, and a unit C represented by the following Chemical Formula 4: [Chemical formula 2] [Chemical formula 3] [Chemical formula 4] In the above Chemical Formula 2, Chemical Formula 3 and Chemical Formula 4, r is an integer of 1 or greater, R1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom, R3 represents a Cn alkyl group in which all hydrogen atoms are replaced by fluorine atoms, R4 represents a Cn-1 alkyl group in which all hydrogen atoms are replaced by fluorine atoms, n is 2 or 3, Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1, R6 and R7 each independently represent a C1 to C5 straight chain alkyl or branched chain alkyl, R8 is null or represents methyl, and m is an integer selected from 1, 2, 3, 4 and 5.

3. The gel polymer electrolyte according to claim 2, wherein Chemical Formula 2 is divided into a unit represented by the following Chemical Formula 2-1 and a unit represented by the following Chemical Formula 2-2: [Chemical formula 2-1] [Chemical formula 2-2] In the above Chemical Formula 2-2, R1 represents an aliphatic hydrocarbon group, an alicyclic hydrocarbon group or an aromatic hydrocarbon group.

4. The gel polymer electrolyte according to claim 3, wherein the aliphatic hydrocarbon group is a C1 to C20 alkylene group; a C1 to C20 alkylene group containing an isocyanate (NCO) group; a C1 to C20 alkoxyene group; a C2 to C20 alkene group; or a C2 to C20 alkynylene group; The alicyclic hydrocarbon group is a substituted or unsubstituted C4 to C20 cycloalkylene group; a substituted or unsubstituted C4 to C20 cycloalkylene group containing an isocyanate (NCO) group; a C4 to C20 cycloalkenylene group; or a C2 to C20 heterocycloalkylene group; and The aromatic hydrocarbon group is a substituted or unsubstituted C6 to C20 arylene group; or a C2 to C20 heteroarylene group.

5. The gel polymer electrolyte according to claim 4, wherein the structure represented by Chemical Formula 2-2 is derived from any one selected from the group consisting of compounds represented by the following Chemical Formulas a to n: [Chemical formula a] [Chemical formula b] [Chemical formula c] [Chemical formula d] [Chemical formula e] [Chemical formula f] [Chemical formula g] [Chemical formula h] [Chemical formula i] [Chemical formula j] [Chemical formula k] [Chemical formula 1] [Chemical formula m] [Chemical formula n] 6. The gel polymer electrolyte according to claim 4, wherein the structure represented by Chemical Formula 2-2 is any one selected from the following Chemical Formulas o to x: [Chemical formula o] [Chemical formula p] [Chemical formula q] [Chemical formula] [Chemical formulas] [Chemical formula t] [Chemical formula] [Chemical formula v] [Chemical formula w] [Chemical formula x] 7 . The gel polymer electrolyte according to claim 2 , wherein Chemical Formula 4 provides (meth)acryloyl groups to both ends of the oligomer represented by Chemical Formula 1.

8. The gel polymer electrolyte according to claim 1, wherein the oligomer comprises a compound represented by the following Chemical Formula 5: [Chemical formula 5] 9 . The gel polymer electrolyte of claim 1 , wherein the weight average molecular weight (Mw) of the oligomer is about 1,000 g / mol to 500,000 g / mol. 10 . The gel polymer electrolyte according to claim 1 , wherein the matrix polymer further comprises inorganic particles in an amount of 5 parts by weight to 700 parts by weight based on 100 parts by weight of the oligomer. 11 . The gel polymer electrolyte according to claim 1 , having a gel content of about 1 wt % or more at a temperature of 25° C. 12 . A lithium ion secondary battery comprising a negative electrode, a positive electrode, and a gel polymer electrolyte, wherein the gel polymer electrolyte is the same as the gel polymer electrolyte defined in any one of claims 1 to 11 .

13. A composition for a gel polymer electrolyte, the composition comprising a lithium salt, a non-aqueous solvent, a polymerization initiator, and an oligomer represented by the following Chemical Formula 1, wherein the content of the oligomer is 0.5 wt % to 20 wt % based on the total weight of the composition for a gel polymer electrolyte: [Chemical formula 1] In the above chemical formula 1, r is an integer of 1 or greater, R1 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group, R2 and R5 each independently represent a C1 to C3 alkyl group in which at least one hydrogen atom is substituted by a fluorine atom, R3 represents a Cn alkyl group in which all hydrogen atoms are substituted by fluorine atoms, R4 represents a Cn-1 alkyl group in which all hydrogen atoms are substituted by fluorine atoms, and n is 2 or 3, Either one of p and q represents 0, or both p and q may represent an integer of 1 or more, and when both p and q represent an integer of 1 or more, the value of p / q is 1 / 9 to 9 / 1, R6 and R7 each independently represent a C1 to C5 straight chain alkyl or branched chain alkyl, R8 is null or represents methyl, and m is an integer selected from 1, 2, 3, 4 and 5.

Citation Information

Patent Citations

  • pyrimidine-5-carboxamide compound

    KR1020220046564A

Cited By

  • Battery cell, battery apparatus, and electrical apparatus

    WO2026000395A1